Nanocellulose/two dimensional nanomaterials composites for advanced supercapacitor electrodes - Liang, Qidi; Wang, Yaxuan; Yang, Yanfan; Xu, Ting; Xu, Ying; Zhao, Qingshuang; Heo, Su-Hak; Kim, Min-Seok; Jeong, Young-Hwan; Yao, Shuangquan; Song, Xueping; Choi, Sun-Eun; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
The problems of energy crisis and environmental pollution are increasing daily, and the development of high-efficiency energy storage technology and green renewable energy is imminent. Nanocellulose, as the biomass-based derivatives material, is biodegradable, maintaining good mechanical flexibility, potent chemical reactivity, and high mechanical strength, which has attracted significant appeal for use in energy storage. Supercapacitors have drawn great attraction in wearable electronics because of their portability and stable performance. In fabricating high-performance flexible supercapacitors, electrodes are significant and require good electrochemical performance and flexibility. In this review, MXene and graphene composited with nanocellulose are reviewed as electrodes for supercapacitors, focusing on the overall electrochemical performance of nanocellulose-based supercapacitors. In addition, the potential of nanocellulose/two dimensional nanomaterials composites in supercapacitors is also discussed.